Development of Multiple Intelligence Based Digital Extracurricular Management Model for High Schools - Filimdity, Elsa K.; Manongga, Danny; Dwikurnaningsih, Yari (LPPM Universitas Pendidikan Mandalika, 2025)
This study aims to develop an extracurricular management model grounded in multiple intelligences theory. Employing the Borg and Gall Research & Development (R&D) model, this study integrates a mixed-methods approach. The model comprises ten stages, with this study reaching five stages, namely small-scale product revisions. Expert validation involved three specialists, while small-scale trials engaged 15 teachers and three high school principals. Data collection methods included interviews, questionnaires, and observations, with qualitative and quantitative descriptive analysis employed. The results show that EXMMIND (Digital Multiple Intelligences Extracurricular Management) is effective, with feasibility tests yielding 89.5% (IT experts), 86% (management experts), and 90% (principals) and 89% (teachers), all categorized as 'very good'. EXMMIND provides students with opportunities for growth and development aligned with their strengths. Schools, as institutions that foster humanization, create extracurricular activities and lifelong provisions that are mastered and carried throughout life. This product is anticipated to be implemented to enhance extracurricular activities grounded in students' potential, interests, and intelligence.